Cultural Values and Their Importance for Ethical Codes in Banking Sector - Lokaj, Aleš; Klimsza, Lucjan (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
This article is one of the results of an interdisciplinary research project between the Department of Civic Education, University of Ostrava and Department of Economics, VŠB – Technical University of Ostrava. The main goal of this research project is the description of relations between society and ethical codes in companies. The initial phase of the project is focused on the banking sector, because we assume that in this sector is the code of ethics mostly used. The aim of this article is analyzing the banking sector in the Czech Republic, its history and present, ownership structure and identifying bank leaders in the Czech Republic, its ethical codes and consistency with cultural values. The final analysis focusses on economic efficiency and the ethical content analysis of selected entities.